Pentingnya Etika Berkomunikasi: Implementasi Seni Berbicara Anti Toxic - Imelda, Bunga; Syafi’i, Chandra Muhamad; Palguna, Daniel Sapta; Rahayu, Desinta Dwi; Chumaeson, Wahyuning (Universitas Pahlawan Tuanku Tambusai, 2025)
Negative communication issues such as verbal bullying and the use of harmful language are major issues at SMP Negeri 5 Boyolali that negatively impact students’ mental health and social well-being. The purpose of this community service is to introduce anti-toxic communication skills and encourage positive interactions in the school environment. Activities are carried out using interactive learning methods that include preparing materials, delivering positive communication theories, and practicing speaking and non-verbal communication skills. The results of the service show an increase in students’ awareness of the importance of constructive communication and a decrease in harmful behavior. This program has succeeded in creating a more supportive learning atmosphere, increasing students’ self-confidence, and supporting a culture of mutual respect in the school.